Blood glucose levels in chronic kidney disease patients with diabetes mellitus at the internist poly of RSUD Dr. H Abdul Moeloek Bandar Lampung - Faizar, Fathia Azzahra; Marsiati, Himmi; Arifandi, Firman; Armelia, Linda (Jurnal Info Sains : Informatika dan Sains, 2024)
Background: High blood glucose levels in Diabetes Mellitus patients can harm renal capillaries. Chronic Kidney Disease caused by Diabetes Mellitus begins with microalbuminuria. Chronic Kidney Disease patients with Diabetes Mellitus at RSUD Dr. H. Abdul Moeloek Bandar Lampung from July 202 to December 2022 there were 127 patiens.Purpose : The aim of this study was to determine blood glucose levels ini Chronic Kidney Disease patients suffering from Diabetes Mellitus at RSUD Dr. H. Abdul Moeloek Bandar Lampung.Method : This research is an observational analytical research with a cross- sectional approach. The sample in this study was calculated using the Slovin formula so that the number of samples used was 99. Data analysts used univariate analysis.Result : from the research result, it was found that 127 patients with Chronic Kidney Disease suffered from Diabetes Mellitus. Chronic Kidney Disease with Diabetes Mellitus was most often found in men, 64 patients (50.4%), in the age group, Chronic Kidney Disease with Diabetes Mellitus was most often found in patients aged 51-60 years, 56 patients (44.1%), while the blood glucose levels of patients with Chronic Kidney Disease with Diabetes Mellitus were most often found in patients with blood glucose levels >180 mg/DL, 76 patients (59.8%). Conclussion : The blood glucose level most often found was >180 mg/DL, namely 76 patients were called the hyperglycemia category and the lowest blood glucose level found was <74 mg/DL, namely 2 patinents were calles the hypoglycemia category.